Evaluation of the Composite Skin Patch Loaded with Bioactive Functional Factors Derived from Multicellular Spheres of EMSCs for Regeneration of Full-thickness Skin Defects in Rats - Zhang, Xuan; Shi, Wentao; Wang, Xun; Zou, Yin; Xiang, Wen; Lu, Naiyan (Current Stem Cell Research & Therapy, 2024)
Background: Transplantation of stem cells/scaffold is an efficient approach for treating tissue injury including full-thickness skin defects. However, the application of stem cells is limited by preservation issues, ethical restriction, low viability, and immune rejection in vivo. The mesenchymal stem cell conditioned medium is abundant in bioactive functional factors, making it a viable alternative to living cells in regeneration medicine. Methods: Nasal mucosa-derived ecto-mesenchymal stem cells (EMSCs) of rats were identified and grown in suspension sphere-forming 3D culture. The EMSCs-conditioned medium (EMSCs-CM) was collected, lyophilized, and analyzed for its bioactive components. Next, fibrinogen and chitosan were further mixed and cross-linked with the lyophilized powder to obtain functional skin patches. Their capacity to gradually release bioactive substances and biocompatibility with epidermal cells were assessed in vitro. Finally, a full-thickness skin defect model was established to evaluate the therapeutic efficacy of the skin patch. Results: The EMSCs-CM contains abundant bioactive proteins including VEGF, KGF, EGF, bFGF, SHH, IL-10, and fibronectin. The bioactive functional composite skin patch containing EMSCs-CM lyophilized powder showed the network-like microstructure could continuously release the bioactive proteins, and possessed ideal biocompatibility with rat epidermal cells in vitro. Transplantation of the composite skin patch could expedite the healing of the full-thickness skin defect by promoting endogenous epidermal stem cell proliferation and skin appendage regeneration in rats. Conclusion: In summary, the bioactive functional composite skin patch containing EMSCs-CM lyophilized powder can effectively accelerate skin repair, which has promising application prospects in the treatment of skin defects.
Keywords: conditioned medium (CM)